Purification of Used Lubricating Oils Using Vacuum Distillation - Ahmed, Dalya J.; Al-Nidawi, Mustafa R.; Chali, Mohammed; Bahjat , Ahmed (Journal of Petroleum Research and Studies, 2024)
Engine oil (EO) is produced by mixing base oil derivatives from crude oil with chemical additives to the lubricity of moving parts and reduce the friction inside the engine. Used lubricating oil (ULO) is one of the hazardous materials that consists of pollution harmful to the environment, it needs to be managed properly. In this work, vacuum distillation technique is used to recycle used lubricating oil. Used lubricating oil samples from two different brands of diesel engine oil (20w-50) and gasoline engine oil (10W-30) are used in this study. Various properties of ULO and recycled oil were characterized such as kinematic viscosity, viscosity index, density, pour point, flash point, Sulphur content, and Fourier transform Infrared spectroscopy FTIR. The yield recycles for ULO of gasoline engines, diesel engines, and mix (gasoline and diesel) by vacuum process were 85%, 74%, and 75% respectively, it was discovered that the sulfur component decreased from 9792.3 ppm of ULO to 405 ppm of yield distillates. The pour point results show an increase from -30 °C of used lubricating oil to -18 and -6 for distillates cut for vacuum distillation, compared to the pour point of Iraqi base oil 40 and 60 Stook (SN150 and SN200) -18 °C and -6 °C